2022
DOI: 10.30541/v41i4iipp.551-566
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Conditions Index: A Composite Measure of Monetary Policy in Pakistan

Abstract: Accurate measures of the size and direction of changes in monetary policy are very important. A number of variables/indicators have been used as a measure of the stance of monetary policy the world over. These include growth rates of monetary aggregates and credit aggregates, short-term interest rate as used by Sims (1992), index of minutes of Federal Open Market Committee (FOMC), as suggested by Friedman and Schwartz (1963) and reintroduced by Romer and Romer (1989), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…The SBP has been using M2 aggregate (i.e., currency + demand deposits + time deposits) for policy purposes on the assumption that the demand for M2 function is stable in Pakistan. Utilizing the estimated money demand function the target rate of growth of M2 is set (Qayyum, 2002).…”
Section: One Of the Important And Crucial Intermediate Target Variablmentioning
confidence: 99%
“…The SBP has been using M2 aggregate (i.e., currency + demand deposits + time deposits) for policy purposes on the assumption that the demand for M2 function is stable in Pakistan. Utilizing the estimated money demand function the target rate of growth of M2 is set (Qayyum, 2002).…”
Section: One Of the Important And Crucial Intermediate Target Variablmentioning
confidence: 99%
“…Previous MCI studies have shown that the interest rate and exchange rate channels need to be jointly evaluated when studying monetary policy and changes to the monetary conditions (Qayyum, 2002). Amador et al (2020) have shown that policies that do not simultaneously address interest rate and exchange rate channels affect capital flows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several ways to construct this composite index. One example is the monetary condition index which is the weighted average of changes in the exchange rate and interest rate relative to a benchmark level (Batini and Turnbull, 2002;Qayyum, 2002). Another example is to use the component derived from the Principal component analysis of various monetary policy instruments (Memon and Jabeen, 2018).…”
Section: Robustness Testmentioning
confidence: 99%